1996
DOI: 10.1002/hep.510240114
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of the Protein Kinase Substrate Annexin I in Human Hepatocellular Carcinoma

Abstract: and chromobindins. 15 AXs were first described as glucocortiAnnexin (AX) constitutes a new family of Ca 2/ -depencoid-inducible inhibitory proteins of phospholipase A 2 . 13,14 dent membrane-binding proteins; 13 of them have been These proteins possess four or eight conserved 70 amino acid described. Among these, annexin-I (AX-I) has displayed repeats, which comprise the core domain, where Ca 2/ -and many biological functions in vitro. Its actual role in vivo, phospholipid-binding functions are located. Annexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Prior studies have demonstrated increased expression of annexin I and͞or II in different tumor types (36)(37)(38)(39)(40). Thus, the extent to which annexin II autoantibodies may occur in tumor types other than lung cancer requires further investigation, in particular, in cancer types in which increased annexin II has been observed previously, as in the case of glioblastoma multiforme (39), pancreatic cancer (40), and acute premyelocytic leukemia (41).…”
Section: Discussionmentioning
confidence: 94%
“…Prior studies have demonstrated increased expression of annexin I and͞or II in different tumor types (36)(37)(38)(39)(40). Thus, the extent to which annexin II autoantibodies may occur in tumor types other than lung cancer requires further investigation, in particular, in cancer types in which increased annexin II has been observed previously, as in the case of glioblastoma multiforme (39), pancreatic cancer (40), and acute premyelocytic leukemia (41).…”
Section: Discussionmentioning
confidence: 94%
“…ANXA1 is a novel biomarker in predicting patients' clinical outcome. However, its expression in cancer remains controversial because it is reduced in certain cancers [12][13][14][15][16]36] , but increased in other cancer types [5,[7][8][9][10] . In the present study, we observed that ANXA1 was downregulated in hilar cholangiocarcinoma specimens compared with normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The following studies revealed that ANXA1 also played a critical role in regulating cell proliferation, apoptosis, and carcinogenesis. Previous studies showed that ANXA1 expression was increased in pancreatic [7] , hepatic [8] , glial [9] and esophageal and esophagogastric junction adenocarcinomas [5,10] . However, recent studies revealed that ANXA1 expression was markedly decreased in esophageal [11] , gastric [12] , thyroid [13] , nasopharyngeal [14] , and breast carcinomas [15,16] , and correlated with tumor differentiation, metastasis, and poor outcome.…”
mentioning
confidence: 95%
“…30) AnxA1 increased in the proliferative hepatocytes after carbon tetrachloride-induced rat liver damage or a partial hepatectomy and in hepatocellullar carcinoma tissue. 31,32) Although the mechanism of action of AnxA3 on DNA synthesis is presently uncertain, the target of AnxA3 may be a common signal transduction pathway, and not necessarily a constitutive or growth factor-mediated one, because the suppression of AnxA3 expression using RNAi not only inhibited the control of DNA synthesis, but also EGF-or HGF-stimulated DNA synthesis, almost to a similar level. In this respect, the findings described below may be relevant to speculations on the mechanism of action of AnxA3 on DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%